DEMETER observations of bursty MF emissions and their relation to ground‐level auroral MF burst. Issue 12 (1st December 2014) - Broughton, M. C.; LaBelle, J.; Parrot, M.
Abstract: A survey of medium frequency (MF) electric field data from selected orbits of the Detection of Electro‐Magnetic Emissions Transmitted from Earthquakes (DEMETER) spacecraft reveals 68 examples of a new type of bursty MF emissions occurring at high latitudes associated with auroral phenomena. These resemble auroral MF burst, a natural radio emission observed at ground level near local substorm onsets. Similar to MF burst, the bursty MF waves observed by DEMETER have broadband, impulsive frequency structure covering 1.5–3.0 MHz, amplitudes of 50–100 μV/m, an overall occurrence rate of ∼0.76% with higher occurrence during active times, and strong correlation with auroral hiss. The magnetic local time distribution of the MF waves observed by DEMETER shows peak occurrence rate near 18 MLT, somewhat earlier than the equivalent peak in the occurrence rate of ground level MF burst, though propagation effects and differences in the latitudes sampled by the two techniques may explain this discrepancy. Analysis of solar wind and SuperMAG data suggests that while the bursty MF waves observed by DEMETER are associated with enhanced auroral activity, their coincidence with substorm onset may not be as exact as that of ground level MF burst. One conjunction occurs in which MF burst is observed at Churchill, Manitoba, within 8 min of MF emissions detected by DEMETER on field lines approximately 1000 km southeast of Churchill. These observations may plausibly be associated with the same auroral event detected by ground level magnetometers at several Canadian observatories. Although it is uncertain, the balance of the evidence suggests that the bursty MF waves observed with DEMETER are the same phenomenon as the ground level MF burst. Hence, theories of MF burst generation in the ionosphere, such as beam‐generated Langmuir waves excited over a range of altitudes or strong Langmuir turbulence generating a range of frequencies within a narrow altitude range, need to be revisited to see whether they predict in situ detection of MF burst. Key Points: DEMETER has observed bursty MF waves in the auroral ionosphere The MF waves resemble MF burst observed at ground level Current theories of MF burst generation should account for in situ observations